Collecting by design : silver and metalwork of the twentieth century from the Margo Grant Walsh collection - O'Brien, Timothy A.; Walsh, Margo Grant; Museum of Fine Arts, Houston (Houston : Museum of Fine Arts, Houston ; New Haven : Distributed by Yale University Press, 2008)
"Margo Grant Walsh is an award-winning interior architect with an impeccable eye for collecting silver. She has amassed an unparalleled collection of more than 800 exquisitely designed and beautifully crafted pieces of silver and metalwork by internationally acclaimed artists and workshops. This book is the first to document her collection"--Provided by publisher.
Issued in connection with the exhibition Designed by Architects: metalwork from the Margo Grant Walsh collection, organized by the Museum of Fine Arts, Houston, and presented there from March 15 to August 3, 2008.
Includes bibliographical references (p.135) and index.
Keywords: Walsh, Margo Grant -- Art collections -- Exhibitions; Art metal-work -- Private collections -- United States -- Exhibitions; Silverwork -- Private collections -- United States -- Exhibitions; Architect-designed art metal-work -- History -- 20th century -- Exhibitions